Competency Improvement Training Program for Inclusive Education in DKI Jakarta Province - Anisa Nur Aqlia; Lina Miftahul Jannah (Business Education Program of Universitas Pendidikan Indonesia, 2022)
Since the issuance of Governor Regulation Number 40 of 2021 concerning the Implementation of Inclusive Education, all schools in DKI Jakarta Province have been mandated to become Inclusive Education Providers. However, the availability of Special Advisor Teachers is still very limited. Therefore, in order to reduce the gap for the lack of Special Advisor Teachers, the DKI Jakarta Provincial Education Office organized a teacher competency improvement training program to improve the competence of educators in supporting teaching and learning activities at Inclusive Education Providers. This study aims to analyze the Teacher Competency Improvement Training Program for Inclusive Education in the Province of DKI Jakarta. The method used in this research is descriptive qualitative with literature study, observation and in-depth interviews with informants. The results of this study is the training methods have been well coordinated so that between UPTs there are no differences in methods. The enthusiasm of the participants varied in each region, due to the online training, some of the participants were still assigned to teach so they did not focus on the training. The evaluation of the training by participants for the organizers and instructor has been carried out through a questionnaire instrument, but the evaluation results are not coordinated with the instructor.